Pneumocystis colonisation is common among hospitalised HIV infected patients with non-Pneumocystis pneumonia. Issue 4 (16th November 2007) - Davis, J L; Welsh, D A; Beard, C B; Jones, J L; Lawrence, G G; Fox, M R; Crothers, K; Morris, A; Charbonnet, D; Swartzman, A; Huang, L
Abstract : Background: When Pneumocystis DNA is recovered from respiratory specimens of patients without Pneumocystis pneumonia (PCP), patients are said to be colonised with Pneumocystis, although the significance of this state is unknown. Understanding risk factors for and outcomes of colonisation may provide insights into the life cycle and transmission dynamics of Pneumocystis jirovecii . Methods: We performed a cross sectional study of the prevalence and clinical predictors of Pneumocystis colonisation in 172 HIV infected, PCP negative inpatients undergoing diagnostic evaluation of 183 episodes of pneumonia at either the Medical Center of Louisiana at New Orleans between 2003 and 2005 or San Francisco General Hospital between 2000 and 2005. DNA was extracted from sputum and bronchoalveolar lavage specimens and amplified using a nested PCR assay at the mitochondrial large subunit (18S) ribosomal RNA locus. Colonisation was deemed present if Pneumocystis DNA was identified by both gel electrophoresis and direct DNA sequencing. Results: 68% (117/172) of all patients were colonised with Pneumocystis . No strong associations with colonisation were identified for any demographic factors. Among clinical factors, having a CD4+ T cell count ⩽50 cells/μl (unadjusted OR 2.4, 95% CI 1.09 to 5.48; p = 0.031) and using PCP prophylaxis (unadjusted OR 0.55, 95% CI 0.29 to 1.07; p = 0.077) were associated with Pneumocystis colonisation, although the latter association may have been due to chance. After adjustment for CD4+ T cell count, use of PCP prophylaxis was associated with a decreased odds of colonisation (adjusted OR 0.45, 95% CI 0.21 to 0.98; p = 0.045). 11 patients who were colonised were subsequently readmitted for evaluation of a second episode of pneumonia; three were found to be colonised again, but none had PCP. Conclusions: The majority of hospitalised HIV infected patients with non-PCP pneumonia are colonised with Pneumocystis . Failure to use co-trimoxazole prophylaxis and severe immunosuppression are associated with an increase in the odds of colonisation. Pneumocystis colonisation among hospitalised patients does not commonly lead to PCP.